Conservation of the Renaissance towns of Southern Poland based on selected examples: an introduction to research - Kuśnierz-Krupa, Dominika; Kuśnierz, Kazimierz; Hryniewicz, Małgorzata; Ivashko, Julia; Bober, Dorota (Problematyka ochrony małych miast renesansowych południowej Polski na wybranych przykładach. Wstęp do badań, 2022)
This paper discusses the conservation of selected historical Renaissance urban layouts located in the Lesser Poland, Subcarpathian and Holy Cross voivodeships. The objective of the study was to analyze previous research on the theory of Renaissance urban design theory in Poland, with a particular emphasis on the areas in question, as well as the typology of the urban layouts founded during this period. An analysis of urban layouts of selected small towns was performed, which also covered their current forms of statutory conservation. The degree of preservation of the layouts’ historical structure was determined, and a proposal of general guidelines for their conservation was formulated.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2022, nr 4 (72), s. 83-90
Keywords: architektura; Renaissance-period urban design; Zakliczyn; Cieszanów; Raków; conservation; revalorization; urbanistyka okresu renesansu; ochrona; rewaloryzacja